The Role Of Private Practices Of State Islamic University Of North Sumatera In The Dissemination Of Information In The Time Of The Covid-19 Pandemic (Pena Cendekia Insani, 2022)
This study aims to determine the efforts made by the Public Relations of the State Islamic University of North Sumatra in disseminating information during the Covid-19 pandemic and to find out the strategies and obstacles of the Public Relations of the State Islamic University of North Sumatra in disseminating information during the Covid-19 pandemic. Theories used in this research are information theory, information media theory, Public Relations and dissonance theory. The subjects of this study were the employees of the Head of the Public Relations Division and the Public Relations Executive of the State Islamic University of North Sumatra who managed the dissemination of information. The location of this research was carried out at the Public Relations Bureau of the State Islamic University of North Sumatra starting from July 5, 2021 until its completion. The method used in this research is the Qualitative Method. The analysis technique used is descriptive qualitative. The result of this research is that the role of Public Relations of the State Islamic University of North Sumatra Public Relations of the State Islamic University of North Sumatra has carried out its role well. This role was very clear when the State Islamic University of North Sumatra opened registration for new student candidates. This proves that public interest continues to increase with the information provided by Public Relations. Of course, the role of public relations is supported by the communication strategy used by public relations through social media to disseminate information during the COVID-19 pandemic.